“Geologia, deformação e idade (U-Pb) do grupo campanário, sequência metassedimentar mesoproterozoica no terreno Rio Apa, sul do Cráton Amazônico” - Cabrera, Rafael Ferreira (2015)
The Campanario sequence is located in the Rio Apa Terrain, south of the Amazonian Craton, municipality of Porto Murtinho (MS). Is an essentially siliciclastic unit formed by layers of quartzitc metaparaconglomerate matrix supported, followed by muscovite metarenite, quartzite with parallel beds, quartz-muscovite schist and gray-green laminate phyllite. This rock maintains contact by erosive and tectonic disagreement with basement rocks, with common areas of low shear diving launch the supracrustal above the granitic basement. Three deformational phases affected these rocks, all of compressive character; the first (F1) caused the folding (D1) and partial transposition of the sedimentary layering (S0), adopting the same orientation of the foliation S1. These folds (D1) are tight, the isoclinal recumbent, preferably N-S sub-horizontal axis. Also generated foliation axial-plane (S1) attitude 97/44. It is observed paragenesis marked by the coexistence of muscovite, biotite, sericite and chlorite, indicating greenschist facies metamorphism, on biotite zone. Subsequent cleavage deformations originated two crenulation, the last incipient; however, these rocks still keep record of sedimentary structures such as stratification and a parallel lamination and cross-tabular and slotted. Ar-Ar analyzes indicate muscovites lock Air system at 1.3 Ga on the first deformation (F1). U-Pb dating LA-MP-ICP-MS in detrital zircons indicate strong contribution of estaterian-orosirian granitoids and gneisses of the basement, and maximum sedimentation age of 1.7 Ga. These rocks had different names and stratigraphic positions, however, field features, stratigraphic and structural/deformation analyzes reported here indicate distinct unit, not yet described in Brazil